Examining the Relationship Between Early Maladaptive Schemas and Alexithymia with Emotional Divorce Among Married Female Students - Poursheykhian, Soudabeh; Alizadeh Darbandi, Hasan; Arian, Reyhaneh (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to investigate the relationship between early maladaptive schemas (EMS), alexithymia, and emotional divorce among married female students, focusing on their predictive roles in marital detachment. Methods: A correlational design was employed with 240 married female students recruited via convenience sampling from Islamic Azad University, Tonekabon Branch (2023–2024 academic year). Participants completed validated self-report measures: the Young Schema Questionnaire-Short Form (YSQ-SF; Young, 1995) assessing EMS across five domains (e.g., Impaired Limits, Other-Directedness), the Toronto Alexithymia Scale (TAS-20; Bagby et al., 1994) measuring alexithymia subscales (Difficulty Identifying Feelings, Difficulty Describing Feelings, Externally Oriented Thinking), and the Gottman Emotional Divorce Questionnaire (GEDQ; Gottman, 1997). Data were analyzed using Pearson’s correlation and stepwise regression via SPSS-26, with significance set at *p* < .01. Findings: Significant correlations emerged between EMS domains, alexithymia, and emotional divorce (*r* = 0.18–0.53, *p* < .01). Stepwise regression revealed Impaired Limits as the strongest predictor (β = 0.39, *p* < .01), explaining 15% of variance, followed by incremental contributions from Difficulty Identifying Feelings (ΔR² = 3%, β = 0.23), Other-Directedness (ΔR² = 1%, β = 0.13), Externally Oriented Thinking (ΔR² = 2%, β = 0.18), and Impaired Autonomy (ΔR² = 2%, β = -0.22), cumulatively accounting for 23% of variance (F = 15.16, *p* < .01). Negative β for Impaired Autonomy suggested suppression effects. Conclusion: EMS and alexithymia significantly predict emotional divorce, with Impaired Limits and emotion-regulation deficits being central drivers. Findings underscore the need for schema-focused interventions (e.g., schema therapy) and emotion-regulation training in marital counseling to mitigate detachment. Future research should explore dyadic interactions and cultural moderators to refine predictive models.